Analisa Stakeholder dalam Program Konsolidasi Tanah di Desa Gadingsari Kecamatan Sanden Kabupaten Bantul - Nur, Yusriana; Sarwadi, Ahmad (Sekolah Tinggi Pertanahan Nasional, 2021)
Land reform is an activity to provide a sense of justice in the control, ownership, use and utilization of land in the context of the welfare of the people who work in agriculture, but in fact the goals to be achieved are not realized because before the success of the land redistribution object has been transferred to other parties, it is necessary to knowing and solving efforts so that premature transfers can be avoided, while the method used in this writing is descriptive normative, meaning to see social problems that occur in the community related to transfers for further analysis based on the results of existing research and regulatory provisions through literature study. The results show that institutionally the implementation of land reform is better than at present, because the implementing organization reaches the village level, in contrast to now only at the district level, including the prevention of the transfer of the object of redistribution, which is regulated in detail so that it is difficult to transfer rights to the land of the object of redistribution. On the other hand, the existence of cooperatives is needed as a form of prevention of diversion.